Diaqua(1,4,8,11-tetraazacyclotetradecane-kappa 4 N 1,N 4,N 8,N 11)copper(II) diheptanoate dihydrate - Tajidi, N.S.A.; Abdullah, N.; Arifin, Z.; Tan, K.W.; Ng, S.W. (International Union of Crystallography, 2010)
The CuII atom in the title salt, [Cu(C(10)H(24)N(4))(H(2)O)(2)][CH(3)(CH(2))(5)CO(2)](2)center dot 2H(2)O, is chelated by the four N atoms of the 1,4,8,11-tetraazacyclotetradecane (cyclam) ligand and is coordinated by two water molecules in a tetragonally Jahn-Teller-distorted octahedral geometry. The CuII atom lies on a center of inversion. The cations, anions and uncoordinated water molecules are linked by N-H...O and O-H...O hydrogen bonds, forming a layer structure parallel to (100). The alkyl chain of the anion is disordered over two positions in a 0.82 (1):0.18 (1) ratio.